Soluble CD163 is an indicator of liver inflammation and fibrosis in patients chronically infected with the hepatitis B virus. Issue 4 (2nd September 2014) - Dultz, G.; Gerber, L.; Farnik, H.; Berger, A.; Vermehren, J.; Pleli, T.; Zeuzem, S.; Piiper, A.; Kronenberger, B.; Waidmann, O.
Summary Soluble CD163 (sCD163), a marker for macrophage activation, was found to be associated with the severity of liver cirrhosis. The aim of the current study was to investigate whether serum sCD163 levels correlate with liver inflammation and fibrosis in patients with chronic hepatitis B virus (HBV) infection. In a retrospective cohort study, serum sCD163 levels were assessed by ELISA together with clinical and laboratory data in 186 patients with chronic HBV infection and 15 healthy controls. The relation between parameters for liver fibrosis and necroinflammation and sCD163 levels was analysed. Additionally, sCD163 was quantified in a subset of follow‐up serum samples after initiation of antiviral treatment. sCD163 levels differed among phases of chronic HBV infection (P < 0.0001), and sCD163 concentrations were associated with inflammatory activity and fibrosis in the liver. sCD163 levels ≥1961 ng/l had a high specificity in the identification of subjects with substantial fibrosis (F ≥ 2). sCD163 concentrations decreased significantly after initiation of antiviral treatment. The correlation of sCD163 levels with necroinflammation and fibrosis and the sCD163 decline under treatment indicates that macrophage activation plays a role in HBV‐related liver pathogenesis.